A healthy donation the Kissamos asclepius (λ 410) – its origin and possible context - Borowka, Dawid (Acta Archaeologica Lodziensia, 2022)
This article publishes a previously unpublished artefact, a marble head of a bearded deity, probably that of Asclepius, currently held in the Kissamos Archeological Museum (cat. nr. Λ 410). The object found its way to the museum as a donation of the educational commission of the 1st primary school in Kissamos, where it was held for an indefinite period. The donation was made in April 1996. In this article an attempt to identify the monument, making use of analogies drawn from ancient art is made along with the presentation of the results of field research undertaken in the area of the city of Kissamos in December 2018 and August 2019, aimed at determining the most likely provenance of the artefact. Finally, an attempt will be made to place the object in the historical and social context of Kissamos, one of the most important centres in Crete during the Roman period, which according to A. Kouremnos had the status of civitas libera.